Innovation, Sustainability, and Small and Medium Enterprise Performance: A Resource-Based View Systematic Literature Review - Ardansyah Ardansyah; M. Yusuf S. Barusman; Habiburahhman Habiburahhman; Defrizal Defrizal (Penerbit Goodwood, 2026)
Purpose: This study systematically examines the relationships among organizational innovation, organizational sustainability, competitive advantage, and Micro, Small, And Medium Enterprise (MSME) performance from a Resource Based View (RBV) perspective. It addresses a research gap by integrating these four constructs into a single conceptual framework, as previous studies have predominantly examined them separately or through limited variable relationships.Research Methodology: A Systematic Literature Review (SLR) was conducted using the PRISMA 2020 protocol. The study reviewed 68 peer-reviewed articles published between 2015 and 2025 from Scopus, Web of Science, and Google Scholar. Data were analyzed through narrative synthesis, thematic clustering, and gap analysis.Results: The findings show that organizational innovation has the strongest positive relationship with MSME performance, while organizational sustainability also contributes significantly. Competitive advantage acts as a mediating mechanism, although its effect varies across different business contexts. Limited studies integrating all constructs indicate a research gap.Conclusions: The review confirms RBV as a relevant foundation for explaining MSME performance through innovation, sustainability, and competitive advantage.Limitations: This study is limited to secondary data from peer-reviewed publications between 2015 and 2025, which may affect broader generalization.Contributions: This study provides an integrated RBV-based framework and future research directions for strengthening MSME competitiveness and sustainability.